2022
DOI: 10.3390/agriculture12081256
|View full text |Cite
|
Sign up to set email alerts
|

Soil Inorganic Carbon as a Potential Sink in Carbon Storage in Dryland Soils—A Review

Abstract: Soil organic carbon (SOC) pool has been extensively studied in the carbon (C) cycling of terrestrial ecosystems. In dryland regions, however, soil inorganic carbon (SIC) has received increasing attention due to the high accumulation of SIC in arid soils contributed by its high temperature, low soil moisture, less vegetation, high salinity, and poor microbial activities. SIC storage in dryland soils is a complex process comprising multiple interactions of several factors such as climate, land use types, farm ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…Because of climate constraints, the soils in arid regions have an inherently low stock of organic C (Table 3). However, they also have a lot of inorganic C, mostly in the form of soil carbonates (Table 3) [61]. On average, Lal [62] reported that dryland ecosystems sequestered between 0.1 and 0.2 Mg ha −1 year −1 of soil inorganic C. In addition to acting as a sink for atmospheric CO 2 , inorganic C in soil may also play a positive function in soil aggregation via the interaction of carbonates with SOM.…”
Section: Soil Organic and Inorganic Carbonmentioning
confidence: 99%
“…Because of climate constraints, the soils in arid regions have an inherently low stock of organic C (Table 3). However, they also have a lot of inorganic C, mostly in the form of soil carbonates (Table 3) [61]. On average, Lal [62] reported that dryland ecosystems sequestered between 0.1 and 0.2 Mg ha −1 year −1 of soil inorganic C. In addition to acting as a sink for atmospheric CO 2 , inorganic C in soil may also play a positive function in soil aggregation via the interaction of carbonates with SOM.…”
Section: Soil Organic and Inorganic Carbonmentioning
confidence: 99%
“…According to the authors, Jones (2003) and Dessalegn et al (2014), uncontrolled erosion causes the removal of basic cations like magnesium and calcium and leaves behind unbalanced acidic cations, resulting in a decline in pH. Low pH in a degraded system lowers the restoration rates and reduces carbon sequestration (Rengel, 2003;Naorem et al, 2022). Variation of soil TOC, TN, and C:N across the vegetation cover practices, indicated by the findings were attributive to the benefits of the terraces as a conservation measure, particularly in highly disturbed systems like farmlands.…”
Section: Discussion Soil Properties Change Across Vegetation Cover ...mentioning
confidence: 99%
“…Agricultural soil carbon sinks in China have significant potential to reduce emissions, representing an important means to cope with climate change. Therefore, it is very important to deeply understand the current situation of agricultural carbon sinks and carbon sources in China, as well as their spatiotemporal evolution over long periods of time, in order to guide the next step of agricultural modernization and low carbon ( Figure 3 ) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Literature Review Of Soil Carbon Sequestrationmentioning
confidence: 99%
“… Natural and anthropogenic factors influencing the formation of soil inorganic carbon in dryland soils (Naorem, A [ 18 ]). …”
Section: Figurementioning
confidence: 99%